Companionship in Insecurity: An Anthropological Perspective on Indonesia-Palestine Relations - Yanuardi Syukur (PT. Student Rihlah Indonesia, 2026)
This research analyzes Indonesia-Palestine relations through the perspective of anthropology of friendship, highlighting how friendships are built, maintained, and mobilized in conditions of insecurity, political ambiguity, and structural violence. Through the study of tricky trust, careful involvement, collective effervescence, and symbolic interaction theory, this paper argues that this relationship cannot be reduced solely to formal diplomatic relations or incidental political solidarity. Rather, it is a form of collective friendship rooted in the experience of colonialism, the suffering experienced by both nations, and a sustained commitment to global justice. Through qualitative analysis of literature, participatory observation of Palestinian solidarity events in Indonesia, and discussions with Palestinian clerics, this paper shows that friendship functions as an alternative relational mechanism. These interactions maintain a collective orientation and serve as moral support when international law and humanitarian regimes face failure or limitations in the context of unequal conflicts. Thus, the findings of this article expand the scope of the anthropology of friendship, which usually focuses on the interpersonal realm, by showing that bonds of friendship can operate at the collective, community, and even transnational levels, offering a new perspective for understanding the dynamics of solidarity in global politics.